Local Drug-Crime Dynamics in a Canadian Multi-Site Sample of Untreated Opioid Users - Manzoni, Patrik (Canadian journal of criminology and criminal justice, 2007)
This multi-site study analysed self-reported involvement in property crime, drug dealing, and sex work, across five Canadian cities, among a sample of 677 illicit opioid and other drug users outside of treatment. First, we assessed drug-use patterns and the extent of illegal income-generating behaviour for each city. We then analysed factors and city interactions contributing to engagement in the respective criminal activities, including drug-use patterns, socio-economic characteristics, and other illegal activities. With this approach we explored city-specific patterns of crime prediction; thus we identified local drug-crime associations. The study sample was recruited by outreach and snowball methods and was assessed by standardized study protocols. Findings revealed substantial differences among the cities regarding both the extent and frequency of illegal activities. In regard to local differences, multiple logistic regression models revealed that crack use was strongly associated with property crime in Toronto, while cocaine use was strongly related with sex work in Montreal and Quebec City. This evidence points to local dynamics of drug cultures that are related to specific criminal activities. Implications for further research and intervention efforts are discussed. [ABSTRACT FROM AUTHOR]